Šiizmdegì sajasi ojlardyṇ damu erekšelìkter = Osobennosti razvitija političeskoj mysli v šiizme - Abylov, T. T. (Chabaršy. Dintanu serijasy, 2015)
The article analyses the formation and evolution of political thought in a Shia current of Islam. The authors reveal peculiarity of Shia understanding of the essence and nature of the political power, the role of spiritual leader, the principles and function of the state. On the basis of deep and substantial analises of the veiw of Shia thinkers and scientists-lawers. Allocating four periods of the development of political thought in the legal doctrine of Shia Islam authors underline the peculiar features of each stage and depict theological basis political and legal view of each era. The volume part of the article is devoted to analys formation, strengthening and evolution of the state foundations of the contemporary Islamic Republic of Iran. In this part of the article researchers open a contribution of such intellectuals of Iran as ayatollah Khomeini, Mohammad Hossein Tabatabai, Abdulkarim Hairi, Mehdi Bazargan, Ali Shariati in the development of political, economic and sociocultural system of contemporary Iran.